Positive electrode active material, battery cell, battery, and electric device
Patent Information
- Application Number
- CN202380045313.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-22
AI Technical Summary
The energy retention rate and initial gram capacity of existing lithium batteries are insufficient, especially during long cycles, the energy attenuation is serious, and the initial gram capacity is low, which limits its application scope.
A cathode active material is used, whose matrix chemical formula is Li[LixNiaCobMncMd]O2. By setting a boron-containing alloy coating layer on the surface of the matrix, including transition metals and boron, the compounds of transition metals and boron have structural stability and high temperature resistance. Improve the migration dynamics of lithium ions and release lithium ions to compensate for consumption during the long cycle of the battery, enhancing the energy retention rate and initial gram capacity of the battery.
Significantly improves the energy retention rate and initial gram capacity of lithium batteries, reduces battery energy loss and polarization in long cycles, extends battery life, and reduces material costs.
Smart Images

Figure CN119318031A_ABST
Abstract
Description
Positive electrode active material, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to positive electrode active materials, battery cells, batteries, and electrical devices. Background Art
[0002] In recent years, lithium batteries have been used in an increasingly diverse range of applications, including energy storage systems such as wind, hydro, thermal, and solar power plants, as well as electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. While lithium batteries have experienced significant development, higher requirements have been placed on their energy retention and energy density.
[0003] Therefore, how to improve the energy retention rate and initial gram capacity of the battery is an urgent problem to be solved.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material, a battery cell, a battery and an electrical device, wherein the energy retention rate and the initial gram capacity of the battery can be improved.
[0006] The first aspect of the present application provides a positive electrode active material, comprising: a matrix, the chemical formula of which is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; a coating layer, the coating layer being arranged on the surface of the substrate, and the coating layer including a boron-containing alloy.
[0007] In the embodiment of the present application, the positive electrode active material includes a substrate and a coating layer provided on the surface of the substrate; further, the chemical formula of the substrate is Li[Li x Ni a Co b Mn c M d]O2, M includes at least one of Mg, B, Al, V, Ti, Zr, Sn, La, P and Mo, and x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, d≥0, and the coating layer is a boron-containing alloy. By providing a coating layer of a boron-containing alloy on the surface of the substrate, the coating layer forms a molten fluid state at a high temperature, has good wettability on the grain boundaries with higher surface energy, and can be evenly distributed on the substrate; and the boron-containing alloy has high electronic conductivity, which can not only well protect the two-coordinate oxygen atoms on the grain boundaries of the substrate, but also improve the migration kinetics of lithium ions on the surface of the positive electrode active material, thereby accelerating the migration speed of active lithium ions in the battery, reducing the energy loss, attenuation and polarization of the battery in long cycles, and thus improving the energy retention rate and initial gram capacity of the battery.
[0008] In some embodiments, the boron-containing alloy includes boron and a transition metal, and the transition metal includes at least one of Co, Hf, Zr, and Ti.
[0009] In the embodiments of this application, the boron-containing alloy can enhance the migration kinetics of lithium ions on the surface of the positive electrode active material, thereby reducing the energy loss and decay of the lithium battery during long cycles. By including a transition metal and boron in the boron-containing alloy, the transition metal and boron compound has good structural stability and high-temperature resistance, which can further improve the battery's energy retention rate.
[0010] In some embodiments, the boron-containing alloy includes CoB n , HfB n 、ZrB n 、TiB n 、WB n At least one of , 0<n≤3.
[0011] In the embodiment of the present application, CoB n , HfB n 、ZrB n 、TiB n 、WB n , where 0<n≤3, not only has good structural stability and high temperature resistance, but also the raw materials are easy to obtain and the preparation is relatively simple. n , HfB n 、ZrB n 、TiB n 、WB n , where 0<n≤3, is arranged on the surface of the substrate as a coating layer, and together with the substrate constitutes the positive electrode active material, which can not only improve the energy retention rate of the battery, but also is conducive to wide application.
[0012] In some embodiments, the boron-containing alloy further includes lithium and oxygen.
[0013] In the embodiments of the present application, a boron-containing alloy comprising a transition metal, lithium, and oxygen is disposed as a coating on the surface of a substrate, and together with the transition metal, a boron-containing alloy serves as the positive electrode active material of a lithium battery. The coating releases lithium ions during the battery's long cycling process. These lithium ions can then participate in the battery's reactions as active lithium ions, compensating for the battery's lithium ion consumption during long cycling, further reducing battery degradation during long cycling and improving the battery's energy retention.
[0014] In some embodiments, the micro stress of the positive electrode active material ranges from 0.05% to 1%, and optionally, ranges from 0.1% to 0.5%.
[0015] In the embodiment of the present application, in order to improve the migration kinetics of lithium ions, the surface of the substrate is coated with a coating layer of a boron-containing alloy, and the two together serve as the positive electrode active material of the battery. However, the stress difference in the micropores of the current positive electrode active material is large, and the material is prone to fatigue, which makes the deintercalation of lithium ions in the positive electrode active material increasingly difficult, resulting in battery energy decay. By maintaining the microstress range of the positive electrode active material at 0.05%-1%, especially 0.1%-0.5%, the overall flexibility of the positive electrode active material can be improved, making it easier for lithium ions to be deintercalated in the positive electrode active material during long battery cycles, thereby further reducing battery energy decay.
[0016] In some embodiments, the peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 20-50, optionally, 25-35.
[0017] In the embodiments of the present application, by maintaining the peak intensities of Mn-O and Ni-O in the positive electrode active material at 20-50, especially 25-35, the structural stability of the surface of the positive electrode active material can be ensured, thereby improving the energy retention of the battery over a long cycle.
[0018] In some embodiments, the coating amount of the coating layer is 200-15000 ppm, optionally, 500-10000 ppm, based on the total weight of the metal elements in the coating layer relative to the total weight of the substrate.
[0019] In the embodiments of the present application, by maintaining the coating amount of the coating layer in the positive electrode active material at 200-15000 ppm, especially 500-10000 ppm, the coating layer can perform its function while saving costs without causing unnecessary waste of the coating layer.
[0020] In some embodiments, the surface residual alkali of the positive electrode active material is 200-2000 ppm (w / w), optionally, 500-1000 ppm (w / w).
[0021] In the embodiments of the present application, when the alkaline substance content in the positive electrode active material is too high, the initial coulombic efficiency and discharge gram capacity of the battery will be low. By setting the surface residual alkali content of the positive electrode active material to 200-2000 ppm (w / w), especially 500-1000 ppm (w / w), the initial gram capacity of the battery can be increased.
[0022] In some embodiments, the specific surface area of the positive electrode active material is 0.5-9 m 2 / g, optionally, 0.7-3.5m 2 / g.
[0023] In the embodiment of the present application, the specific surface area of the positive electrode active material is appropriately reduced to enrich the pores of the positive electrode active material, which helps to increase the initial gram capacity of the battery. However, if the specific surface area is too large, the positive electrode active material will become loose, which is not conducive to the back and forth intercalation and deintercalation of metal ions. By making the specific surface area of the positive electrode active material 0.5-9m 2 / g, especially 0.7-3.5m 2 / g, which helps the normal deintercalation of metal ions in the positive electrode active material.
[0024] In some embodiments, the oxygen deficiency of the positive electrode active material is 1.5-4, optionally, 1.8-3.5.
[0025] In the embodiments of the present application, oxygen defects in the positive electrode active material can change the local electronic structure of the material, thereby generating active lithium ion adsorption sites and increasing the lithium ion transport rate. By setting the oxygen defect ratio of the positive electrode active material to 1.5-4, and particularly 1.8-3.5, the migration kinetics of lithium ions can be further improved, thereby further improving the cycle performance and energy density of the battery.
[0026] In some embodiments, the volume average particle size Dv50 of the positive electrode active material is 2-20 μm, optionally, 5-12 μm.
[0027] In the embodiment of the present application, by maintaining the volume average particle size Dv50 of the positive electrode active material at 2-20 μm, especially 5-12 μm, the battery can have a higher discharge capacity and first coulombic efficiency, and the possibility of the positive electrode active material becoming loose and the lithium ion intercalation and deintercalation being unstable can be reduced.
[0028] In some embodiments, the compacted density of the positive electrode active material is 2-3.5 g / cm 3, optionally, 2.6-3.5 g / cm 3 .
[0029] In the embodiment of the present application, if the compaction density of the positive electrode active material is too low, the electrolyte may penetrate into the positive electrode active material, causing serious side reactions, causing the battery to decay seriously during long cycles. 3 , especially 2.6-3.5g / cm 3 , which helps to further improve the battery's energy retention rate.
[0030] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps: providing a substrate, the chemical formula of which is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; dispersing the matrix into an acidic solution and stirring to obtain a matrix mixed solution, optionally, the pH of the acidic solution is 1-3; solidifying and drying the matrix mixed solution to obtain a matrix mixed powder; mixing the matrix mixed powder with a coating layer powder to obtain a positive electrode active material precursor, wherein the coating layer powder includes a boron-containing alloy; sintering the positive electrode active material precursor to obtain the positive electrode active material, wherein the positive electrode active material includes: the matrix, wherein the chemical formula of the matrix is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; the coating layer is arranged on the surface of the substrate, and the coating layer includes the boron-containing alloy.
[0031] In the embodiment of the present application, by placing the substrate in an acidic solution with a pH value of 1-3 and then mixing it with the coating layer powder, the residual alkali on the surface of the substrate can be removed in a milder manner to avoid dissolving the active substances in the positive electrode active material, which helps to increase the gram capacity of the battery and thus increase the energy density of the battery.
[0032] In some embodiments, the acid in the acidic solution includes at least one of sulfuric acid, nitric acid, ammonium persulfate, citric acid, oxalic acid, sodium citrate, ammonium citrate, ammonium hydrogen citrate, fruit acid, salicylic acid, succinic acid, or succinic anhydride.
[0033] In the embodiments of the present application, the acid in the acidic solution includes at least one of sulfuric acid, nitric acid, ammonium persulfate, citric acid, oxalic acid, sodium citrate, ammonium citrate, ammonium hydrogen citrate, fruit acid, salicylic acid, succinic acid or succinic anhydride, that is, the substrate is treated in an acidic solution containing any one of the above acids. These acidic solutions are relatively mild and will not dissolve the active substances in the substrate.
[0034] In some embodiments, the acidic solution further comprises ethanol or water.
[0035] In the embodiments of the present application, the acidic solution also includes ethanol or water. Both ethanol and water are good solvents for dissolving acids such as succinic acid and succinic anhydride. By including ethanol or water in the acidic solution, the succinic acid and succinic anhydride can be dissolved uniformly and sufficiently, thereby uniformly treating the substrate.
[0036] In some embodiments, the mass ratio of the acidic solution to the matrix is 6-35, optionally, 10-20.
[0037] In the present embodiment, an acid such as succinic acid or succinic anhydride is dissolved in ethanol or water to form an acidic solution for treating the substrate. By making the mass ratio of the acidic solution to the substrate 6-35, especially 10-20, the residual alkali on the surface of the substrate can be fully treated.
[0038] In some embodiments, the mass fraction of the acid in the acidic solution is 0.1%-30%, optionally, 10%-20%.
[0039] In the embodiment of the present application, by making the mass fraction of the acid in the acidic solution 0.1%-30%, especially 10%-20%, the residual alkali on the surface of the substrate can be removed in a milder manner.
[0040] In some embodiments, sintering the cathode active material precursor includes sintering the cathode active material precursor in an oxygen atmosphere or an inert gas atmosphere.
[0041] In the embodiment of the present application, unnecessary side reactions can be avoided by sintering the positive electrode active material precursor in an oxygen atmosphere or an inert gas atmosphere.
[0042] In some embodiments, the sintering temperature in the inert gas atmosphere is 250-400°C.
[0043] In the embodiment of the present application, when an inert gas is used to sinter the positive electrode active material precursor, the sintering temperature is maintained at 250-400° C., so that the positive electrode active material precursor can be completely sintered.
[0044] In some embodiments, the sintering temperature in an oxygen atmosphere is 500-700°C.
[0045] In the embodiment of the present application, when oxygen is used to sinter the cathode active material precursor, the sintering temperature is maintained at 500-700° C., so that the cathode active material precursor can be completely sintered.
[0046] In some embodiments, the sintering time is 3-10 hours.
[0047] In the embodiment of the present application, the positive electrode active material precursor can be completely sintered by setting the sintering time of the positive electrode active material precursor to 3-10 hours.
[0048] The third aspect of the present application provides a battery cell, comprising the positive electrode active material described in any one of the embodiments of the first aspect of the present application or the positive electrode active material prepared by the method for preparing a positive electrode active material described in the second aspect.
[0049] A fourth aspect of the present application provides a battery, comprising the battery cell described in the third aspect of the present application.
[0050] The fifth aspect of the present application provides an electrical device comprising the battery described in the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0052] FIG1 is a schematic structural diagram of a positive electrode active material according to an embodiment of the present application;
[0053] FIG2 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0054] FIG3 is a schematic structural diagram of a battery cell according to another embodiment of the present application;
[0055] FIG4 is a schematic structural diagram of a battery according to an embodiment of the present application;
[0056] FIG5 is a schematic diagram of a vehicle according to an embodiment of the present application. DETAILED DESCRIPTION
[0057] The following describes in detail embodiments of the positive electrode active material, battery cell, battery, and electrical device of the present application, with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0058] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of specific range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0060] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0061] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0062] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0063] The terms "above", "below", "greater than" or "less than" as used in this application are inclusive of the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".
[0064] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0065] Lithium batteries are widely used in consumer electronics due to their high energy density, high power density, and long cycle life. In recent years, with the continuous development of electric vehicles and energy storage systems, the requirements for batteries have also continued to increase. Therefore, it is particularly important to develop large-scale energy storage systems with high initial gram capacity and stable energy retention.
[0066] For some existing positive electrode materials, LiCoO2 has a strong oxidation effect on the electrolyte during deep charging and the damage to its own structure caused by excessive lithium removal, so its actual available capacity is only about half of its theoretical capacity; LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and LiNi 1 / 2 Mn 1 / 2 Although O2 and other materials have reduced material costs and toxicity and significantly improved material safety, the actual specific capacity of these layered structure materials has not made a big breakthrough; three-dimensional tunnel structure spinel positive electrode materials, such as LiMnO4, LiNi 0.5 Mn 1.5 Although O4 and polyanion cathode materials have high safety performance, the theoretical specific capacity of these materials is far from meeting the performance requirements of high-energy lithium batteries for cathode materials. Therefore, layered lithium-rich manganese-based materials with high theoretical capacity exceeding 230mAh / g have become one of the important candidate cathode materials for next-generation lithium batteries.
[0067] However, the electronic conductivity of lithium-rich manganese-based positive electrode materials is relatively low, and the battery polarization phenomenon is serious during the cycle, resulting in rapid battery energy decay, especially in long cycles, when the energy decay is very serious. In addition, when lithium-rich manganese-based materials are used as positive electrode materials for lithium batteries, the initial gram capacity of lithium batteries is also low. These shortcomings have become a technical bottleneck that restricts the application of lithium-rich manganese-based positive electrode materials. In response to the above-mentioned disadvantage of rapid energy decay, most existing technologies use conductive carbon coating, but using this solution may reduce the manganese element in the lithium-rich manganese-based materials, causing distortion of the internal structure of the material and affecting the stability of the lithium-rich manganese-based materials; in response to the above-mentioned disadvantage of low initial gram capacity, most existing technologies use strong acid to treat the lithium-rich manganese-based materials, but using this solution will leach active lithium on the surface of the material, thereby reducing the energy density of the battery. Therefore, how to develop a large-scale energy storage system with high initial gram capacity and cyclically stable energy retention rate is particularly important.
[0068] The positive electrode active material, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.
[0069] [Positive electrode active material]
[0070] The first aspect of the present application provides a positive electrode active material. FIG1 is a schematic structural diagram of a positive electrode active material according to an embodiment of the present application. The positive electrode active material 31 includes a matrix, the chemical formula of which is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; the coating layer 312 is disposed on the surface of the substrate 311, and the coating layer 312 includes a boron-containing alloy.
[0071] Research has found that coating the surface of the substrate 311 with a coating layer 312 made of a boron-containing alloy can not only improve the energy retention rate of the battery, but also improve the initial gram capacity of the battery.
[0072] By providing a coating layer 312 on the surface of the substrate 311, the coating layer 312 is a boron-containing alloy. The coating layer 312 forms a molten fluid state at high temperatures, has good wettability at grain boundaries with high surface energy, and can be relatively evenly distributed on the substrate 311. In addition, the boron-containing alloy has high electronic conductivity, which not only effectively protects the di-coordinated cations on the grain boundaries of the substrate 311, but also improves the migration kinetics of lithium ions on the surface of the positive electrode active material 31, thereby accelerating the migration speed of active lithium ions in the battery, reducing the battery's energy loss, attenuation, and polarization during long cycles, and thus improving the battery's energy retention rate and initial gram capacity.
[0073] In some embodiments, the boron-containing alloy includes boron and a transition metal, and the transition metal includes at least one of Co, Hf, Zr, and Ti.
[0074] In the above scheme, by making the boron-containing alloy include transition metal and boron, the compound composed of transition metal and boron has good structural stability and high temperature resistance, which can further improve the energy retention rate of the battery.
[0075] In some embodiments, the boron-containing alloy includes CoB n , HfB n 、ZrB n 、TiB n 、WB n At least one of , 0<n≤3.
[0076] In the above scheme, by making CoB n , HfB n 、ZrB n 、TiB n 、WB n , where 0<n≤3, is provided as a coating layer 312 on the surface of the substrate 311 and together with the substrate 311 constitutes the positive electrode active material 31. CoB n 、 HfB n 、ZrB n 、TiB n 、WB n It not only has good structural stability and high temperature resistance, but also the raw materials are easy to obtain and the preparation is relatively simple, which can not only improve the cycle performance of the battery, but also facilitate its wide application.
[0077] In some embodiments, the boron-containing alloy further includes lithium and oxygen.
[0078] In the above scheme, by applying a boron-containing alloy comprising a transition metal, lithium, and oxygen as a coating layer 312 on the surface of a substrate 311, and together with the coating layer 312 serving as the positive electrode active material 31 of a lithium battery, the coating layer releases lithium ions during the battery's long cycling. These lithium ions can then participate in the battery's reactions as active lithium ions, compensating for lithium ion consumption during long cycling, further reducing battery degradation during long cycling, and improving the battery's cycling performance.
[0079] In some embodiments, the micro stress of the positive electrode active material 31 ranges from 0.05% to 1%, and optionally, from 0.1% to 0.5%.
[0080] In the above scheme, by maintaining the microstress of the positive electrode active material 31 within the range of 0.05%-1%, and particularly 0.1%-0.5%, the overall flexibility of the positive electrode active material can be improved, thus preventing fatigue of the positive electrode active material 31, which would make the intercalation and deintercalation of lithium ions increasingly difficult. This means that during long battery cycles, the intercalation and deintercalation of lithium ions in the positive electrode active material becomes easier, thereby further reducing battery capacity decay and improving cycle performance.
[0081] It should be noted that the microstress of a material refers to the stress between the microstructures of the material. The scale of its action is on the same order of magnitude as the grain size, so that the balance is maintained within or between grains.
[0082] In some embodiments, the peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 20-50, optionally, 25-35.
[0083] In the above scheme, by maintaining the peak intensity of Mn-O and Ni-O in the positive electrode active material at 20-50, especially 25-35, the structural stability of the surface of the positive electrode active material can be ensured, thereby improving the performance stability of the long cycle of the battery.
[0084] In some embodiments, the coating amount of the coating layer 312 is 200-15000 ppm, optionally 500-10000 ppm, based on the total weight of the metal elements in the coating layer 312 relative to the total weight of the substrate 311 .
[0085] In the above solution, by maintaining the coating amount of the coating layer 312 in the positive electrode active material 31 at 200-15000 ppm, especially 500-10000 ppm, the coating layer 312 can perform its function while saving costs and avoiding unnecessary waste of the coating layer 312.
[0086] In some embodiments, the residual alkali on the surface of the positive electrode active material 31 is 200-2000 ppm (w / w), optionally, 500-1000 ppm (w / w).
[0087] In the above scheme, by making the surface residual alkali of the positive electrode active material 31 200-2000 ppm (w / w), especially 500-1000 ppm (w / w), the first coulombic efficiency and discharge capacity of the battery can be improved, thereby improving the energy density of the battery.
[0088] In some embodiments, the specific surface area of the positive electrode active material 31 is 0.5-9 m 2 / g, optionally, 0.7-3.5m 2 / g.
[0089] In the above scheme, by making the specific surface area of the positive electrode active material 31 0.5-9m 2 / g, especially 0.7-3.5m 2 / g, which helps the normal insertion and extraction of lithium ions in the positive electrode active material 31.
[0090] In some embodiments, the oxygen deficiency of the positive electrode active material 31 is 1.5-4, optionally, 1.8-3.5.
[0091] In the above solution, by setting the oxygen deficiency of the positive electrode active material 31 to 1.5-4, especially 1.8-3.5, it helps to further improve the migration kinetics of lithium ions, thereby further improving the cycle performance and energy density of the battery.
[0092] It should be noted that oxygen defects refer to defects in the oxygen element in the oxide material, which may be defects in quantity or in morphology.
[0093] In some embodiments, the volume average particle size Dv50 of the positive electrode active material 31 is 2-20 μm, or alternatively, 5-12 μm.
[0094] In the above scheme, by maintaining the volume average particle size Dv50 of the positive electrode active material 31 at 2-20μm, especially 5-12μm, the battery can have a higher discharge capacity and first coulombic efficiency, and can also prevent the positive electrode active material 31 from becoming loose, which may cause unstable intercalation and deintercalation of lithium ions therein.
[0095] It should be noted that the volume average particle size Dv50 herein means that particles larger than and smaller than this particle size each account for 50% in the positive electrode active material 31 .
[0096] In some embodiments, the compacted density of the positive electrode active material 31 is 2-3.5 g / cm 3, optionally, 2.6-3.5 g / cm 3 .
[0097] In the above scheme, if the compaction density of the positive electrode active material 31 is too low, the electrolyte may penetrate into the positive electrode active material 31, causing serious side reactions and causing the battery to degrade seriously during long cycles. 3 , especially 2.6-3.5g / cm 3 , which helps to further improve the energy density of the battery.
[0098] The present application also provides a method for preparing a positive electrode active material, the method comprising:
[0099] Provide a matrix, the chemical formula of the matrix is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0.
[0100] The matrix is dispersed in an acidic solution and stirred to obtain a matrix mixed solution, wherein the pH of the acidic solution is 2-3.
[0101] The matrix mixed solution is solidified and dried to obtain matrix mixed powder.
[0102] The matrix mixed powder is mixed with the coating layer powder to obtain a positive electrode active material precursor.
[0103] The positive electrode active material precursor is sintered to obtain the positive electrode active material, which includes a matrix, the chemical formula of which is Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; the coating layer is arranged on the surface of the substrate, and the coating layer includes a boron-containing alloy.
[0104] In the above scheme, by placing the substrate in an acidic solution with a pH value of 1-3 and then mixing it with the coating layer powder, the residual alkali on the surface of the substrate can be removed in a relatively gentle manner to avoid dissolving the active substances in the positive electrode active material, which helps to increase the battery's gram capacity and thus increase the battery's energy density.
[0105] In some embodiments, the acid in the acidic solution includes at least one of sulfuric acid, nitric acid, ammonium persulfate, citric acid, oxalic acid, sodium citrate, ammonium citrate, ammonium hydrogen citrate, fruit acid, salicylic acid, succinic acid, or succinic anhydride.
[0106] In the above scheme, the acid in the acidic solution includes at least one of sulfuric acid, nitric acid, ammonium persulfate, citric acid, oxalic acid, sodium citrate, ammonium citrate, ammonium hydrogen citrate, fruit acid, salicylic acid, succinic acid or succinic anhydride. That is, the substrate is treated in an acidic solution containing any of the above acids. These acidic solutions are relatively mild and will not dissolve the active substances in the substrate.
[0107] In some embodiments, the acidic solution further comprises ethanol or water.
[0108] In the above embodiment, the acidic solution also includes ethanol or water. Both ethanol and water are good solvents for dissolving acids such as succinic acid and succinic anhydride. By including ethanol or water in the acidic solution, the acid such as succinic acid and succinic anhydride can be dissolved uniformly and fully, thereby uniformly treating the substrate.
[0109] In some embodiments, the mass ratio of the acidic solution to the matrix is 6-35, optionally, 10-20.
[0110] In the above scheme, the residual alkali on the surface of the substrate can be fully treated by making the mass ratio of the acidic solution to the substrate 6-35, especially 10-20.
[0111] In some embodiments, the mass fraction of the acid in the acidic solution is 0.1%-30%, optionally, 10%-20%.
[0112] In the above solution, by making the mass fraction of the acid in the acidic solution 0.1%-30%, especially 10%-20%, the residual alkali on the surface of the substrate can be removed in a milder manner.
[0113] In some embodiments, the cathode active material precursor is sintered in an oxygen atmosphere or an inert gas atmosphere.
[0114] In the above scheme, unnecessary side reactions can be avoided by sintering the positive electrode active material precursor in an oxygen atmosphere or an inert gas atmosphere.
[0115] In some embodiments, the sintering temperature in an inert gas atmosphere is 250-400°C.
[0116] In the above solution, when an inert gas is used to sinter the positive electrode active material precursor, the sintering temperature is maintained at 250-400° C., so that the positive electrode active material precursor can be completely sintered.
[0117] In some embodiments, the sintering temperature in an oxygen atmosphere is 500-700°C.
[0118] In the above solution, when oxygen is used to sinter the positive electrode active material precursor, the sintering temperature is maintained at 500-700° C., so that the positive electrode active material precursor can be completely sintered.
[0119] In some embodiments, the sintering time is 3-10 hours.
[0120] In the above solution, by setting the sintering time of the positive electrode active material precursor to 3-10 hours, the positive electrode active material precursor can be completely sintered.
[0121] [Positive electrode]
[0122] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material described in any one of the above embodiments.
[0123] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0124] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0125] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0126] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0127] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0128] [Negative electrode]
[0129] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0130] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0131] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0132] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0133] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0134] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0135] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0136] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0137] [Electrolyte]
[0138] The electrolyte conducts ions between the positive electrode and the negative electrode.
[0139] In some embodiments, the electrolyte further comprises a solvent. The solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0140] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0141] [Isolation film]
[0142] In some embodiments, the lithium battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0143] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0144] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0145] In some embodiments, the lithium battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0146] In some embodiments, the outer packaging of the lithium battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the lithium battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0147] The present application has no particular limitation on the shape of the lithium battery, which can be cylindrical, square, or any other shape. For example, FIG2 shows a square-structured battery cell 300 as an example.
[0148] In addition, the present application does not limit the type of lithium battery. The battery cell 300 can be a lithium ion battery or a lithium metal battery. The following embodiments are described using a lithium ion battery as an example.
[0149] Figure 3 is a schematic structural diagram of a battery cell in another embodiment of the present application. In some embodiments, referring to Figure 3, the outer packaging may include a shell 31 and a cover plate 33. Among them, the shell 31 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 31 has an opening connected to the receiving cavity, and the cover plate 33 can be covered on the opening to close the receiving cavity. The positive electrode, the negative electrode and the solid electrolyte can form an electrode assembly 32 through a winding process or a lamination process. The electrode assembly 32 is encapsulated in the receiving cavity. The number of electrode assemblies 32 contained in the battery cell 300 can be one or more, and those skilled in the art can select according to specific actual needs.
[0150] Figure 4 is a schematic diagram of the structure of a battery 500 according to one embodiment of the present application. As shown in Figure 4 , in battery 500, multiple battery cells 300 may be arranged sequentially along the length of battery 500. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 300 may be secured together using fasteners.
[0151] Continuing with Figure 4 , the battery 500 may include a battery box and a plurality of battery cells 300 disposed within the battery box. The battery box includes an upper box body 501 and a lower box body 502. The upper box body 501 can cover the lower box body 502 and form an enclosed space for accommodating the battery cells 300. The plurality of battery cells 300 may be arranged in any manner within the battery box.
[0152] In some embodiments, battery cells may be assembled into a battery module first. The battery module may contain one or more battery cells. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.
[0153] In some embodiments, the battery modules may be assembled into a battery. The battery may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery.
[0154] In addition, the present application also provides an electric device, which includes at least one of the positive electrode active material, battery cell, or battery provided in the present application. The battery cell or battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0155] For example, Figure 5 is a structural diagram of a vehicle according to an embodiment of the present application. As shown in Figure 5, vehicle 1 can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 400, a controller 600 and a battery 500 can be provided inside the vehicle 1, and the controller 600 is used to control the battery 500 to supply power to the motor 400. For example, a battery 500 can be provided at the bottom, front or rear of the vehicle 1. The battery 500 can be used to power the vehicle 1. For example, the battery 500 can be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements of the vehicle 1 during startup, navigation and operation. In another embodiment of the present application, the battery 500 can not only serve as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.
[0156] As the electrical device, a positive electrode active material, a battery cell or a battery can be selected according to its usage requirements.
[0157] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell or a battery can be used.
[0158] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be lightweight and thin, and may use a battery cell as a power source.
[0159] [Example]
[0160] The following examples of the present application are described. The examples described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0161] [Example 1]
[0162] 1. Preparation of lithium-ion batteries
[0163] 1.1) Preparation of positive electrode
[0164] 1.11) Preparation of substrate: Ni 0.35 Co 0.05 Mn 0.60 (OH)2 and lithium hydroxide are weighed in a molar ratio of 1.0:1.25 and mixed in a high-speed mixer; the mixed materials are sintered in an air atmosphere for 10 to 15 hours at a sintering temperature of 780 to 900°C and a heating rate of 2 to 5°C / min to obtain a primary sintered positive electrode intermediate product 1, which is then mechanically ground and vibrated to obtain a lithium-rich manganese-based positive electrode material matrix, hereinafter referred to as the matrix, whose chemical formula is Li[Li 0.11 Ni 0.31 Co 0.04 Mn 0.54 ]O2.
[0165] 1.12) Preparation of positive electrode active material: Dissolve ammonium citrate in deionized water to form an acidic solution with a pH of 2.57; then stir and pickle with a substrate weighed at a certain liquid-to-solid ratio for 0.5 h while stirring at a rate of 900 r / min; after pickling, filter, rinse with deionized water, filter, and then dry at 80°C for 10 h; then mechanically grind and vibrate to obtain a matrix mixed powder; the matrix mixed powder obtained in the above step and cobalt boride (CoB) are mixed in a mass ratio of 1:0.003 and placed in a furnace for a second sintering in an air atmosphere for 10 h at a sintering temperature of 450°C and a heating rate of 2°C / min. The sintered material is mechanically grinded and vibrated to obtain a lithium-sodium manganese composite-based positive electrode active material. Among them, the micro stress of the positive electrode active material is 0.30%, the peak intensity ratio of Mn-O to Ni-O is 30, the CoB coating amount is 2000ppm, the surface residual alkali is 500ppm (w / w), and the specific surface area is 0.8m 2 / g, oxygen deficiency is 2, and particle size is 7μm.
[0166] 1.13) Preparation of positive electrode sheet: The positive electrode active material, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) prepared above were mixed with secondary dry materials at a mass ratio of 96:2:2 for 30 minutes; N-methylpyrrolidone (NMP) solvent was added and stirred rapidly under vacuum conditions to form a positive electrode slurry. The positive electrode slurry was evenly coated on both sides of an aluminum foil with a thickness of 12 μm. The coated electrode sheet was dried in an oven at 100-130°C for half an hour and then taken out to obtain a positive electrode sheet. Among them, the positive electrode active material loading of the positive electrode sheet is 21.5 mg / cm 2 .
[0167] 1.2) Preparation of negative electrode: Prepare the negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener carbon methyl cellulose sodium (CMC) in a weight ratio of 90:5:2:2:1, stir and mix them thoroughly in a deionized water solvent system to obtain negative electrode slurry. Apply the negative electrode slurry on copper foil, dry it, and cold press it to obtain the negative electrode sheet.
[0168] 1.3). Diaphragm: Use polyethylene (PE) film as the separator.
[0169] 1.4) Electrolyte: 1 mol / L LiPF6 / (EC+EMC+DMC), the volume ratio of EC, EMC, and DMC in the solvent is 1:1:1.
[0170] 1.5) Assembly of lithium-ion batteries: The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed into an aluminum casing, the top cover is welded, and the electrolyte is injected after drying. After standing, formation, sealing welding, aging, and capacity testing, a lithium-ion battery is obtained.
[0171] [Example 2]
[0172] The preparation of the lithium-ion battery of Example 2 is substantially the same as that of Example 1, except that in the preparation of the positive electrode active material, the matrix material and TiB2 are mixed at a mass ratio of 1:0.003.
[0173] [Example 3]
[0174] The preparation of the lithium-ion battery of Example 3 is substantially the same as that of Example 1, except that in the preparation of the positive electrode active material, the matrix material and HfB2 are mixed at a mass ratio of 1:0.003.
[0175] [Example 4]
[0176] The preparation of the lithium ion battery of Example 4 is substantially the same as that of Example 1, except that the microstress of the positive electrode active material is 0.10%.
[0177] [Example 5]
[0178] The preparation of the lithium-ion battery of Example 5 is substantially the same as that of Example 1, except that the microstress of the positive electrode active material is 0.50%.
[0179] [Example 6]
[0180] The preparation of the lithium-ion battery of Example 6 is substantially the same as that of Example 1, except that the peak intensity ratio of Mn—O to Ni—O of the positive electrode active material is 35.
[0181] [Example 7]
[0182] The preparation of the lithium-ion battery of Example 7 is substantially the same as that of Example 1, except that the peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 25.
[0183] [Example 8]
[0184] The preparation of the lithium-ion battery of Example 8 is basically the same as that of Example 1, except that the coating amount of CoB is 1000 ppm.
[0185] [Example 9]
[0186] The preparation of the lithium-ion battery of Example 9 is basically the same as that of Example 1, except that the coating amount of CoB is 5000 ppm.
[0187] [Example 10]
[0188] The preparation of the lithium-ion battery of Example 10 is substantially the same as that of Example 1, except that the residual alkali on the surface of the positive electrode active material is 800 ppm (w / w).
[0189] [Example 11]
[0190] The preparation of the lithium ion battery of Example 11 is substantially the same as that of Example 1, except that the residual alkali on the surface of the positive electrode active material is 1000 ppm (w / w).
[0191] [Example 12]
[0192] The preparation of the lithium-ion battery of Example 12 is basically the same as that of Example 1, except that the specific surface area of the positive electrode active material is 2.3 m 2 / g.
[0193] [Example 13]
[0194] The preparation of the lithium-ion battery of Example 13 is basically the same as that of Example 1, except that the specific surface area of the positive electrode active material is 1.5 m 2 / g.
[0195] [Example 14]
[0196] The preparation of the lithium-ion battery of Example 14 is basically the same as that of Example 1, except that the specific surface area of the positive electrode active material is 3 m 2 / g.
[0197] [Example 15]
[0198] The preparation of the lithium ion battery of Example 15 is basically the same as that of Example 1, except that the oxygen deficiency of the positive electrode active material is 2.5.
[0199] [Example 16]
[0200] The preparation of the lithium-ion battery of Example 16 is basically the same as that of Example 1, except that the particle size of the positive electrode active material is 10 μm.
[0201] [Example 17]
[0202] The preparation of the lithium-ion battery of Example 17 is basically the same as that of Example 1, except that the preparation of the matrix material is as follows: Ni 0.35 Co 0.05 Mn 0.60(OH)2, lithium hydroxide, and MgO are weighed in a molar ratio of 1.0:1.25:0.0025 and mixed in a high-speed mixer; the mixed materials are sintered in an air atmosphere for 10-15 hours at a sintering temperature of 780-900°C and a heating rate of 2-5°C / min to obtain a positive electrode intermediate product 1 after primary sintering; the positive electrode intermediate product 1 is mechanically ground and vibrated to obtain a lithium-rich manganese-based positive electrode material matrix, hereinafter referred to as the matrix, and the chemical formula of the matrix is Li[Li 0.11 Ni 0.31 Co 0.04 Mn 0.535 Mg 0.005 ]O2.
[0203] [Example 18]
[0204] The preparation of the lithium-ion battery of Example 18 is basically the same as that of Example 17, except that in the preparation of the positive electrode active material, the matrix material and TiB2 are mixed at a mass ratio of 1:0.003.
[0205] [Example 19]
[0206] The preparation method of the lithium ion battery of Example 19 is basically the same as that of Example 1, except that the preparation method of the matrix material is as follows: Ni 0.35 Co 0.05 Mn 0.60 (OH)2, lithium hydroxide, and MoS2 are weighed in a molar ratio of 1.0:1.25:0.0025 and mixed in a high-speed mixer; the mixed materials are sintered in an air atmosphere for 10-15 hours at a sintering temperature of 780-900°C and a heating rate of 2-5°C / min to obtain a positive electrode intermediate product 1 after a single sintering; the positive electrode intermediate product 1 is mechanically ground and vibrated to obtain a lithium-rich manganese-based positive electrode material matrix, hereinafter referred to as the matrix, and the chemical formula of the matrix is Li[Li 0.11 Ni 0.31 Co 0.04 Mn 0.535 Mo 0.005 ]O2.
[0207] [Example 20]
[0208] The preparation of the lithium-ion battery of Example 20 is basically the same as that of Example 1, except that the peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 10.
[0209] [Example 21]
[0210] The preparation of the lithium-ion battery of Example 21 is basically the same as that of Example 1, except that the peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 100.
[0211] [Example 22]
[0212] The preparation of the lithium-ion battery of Example 22 is basically the same as that of Example 1, except that the coating amount of CoB is 100 ppm.
[0213] [Example 23]
[0214] The preparation of the lithium-ion battery of Example 23 is basically the same as that of Example 1, except that the coating amount of CoB is 20000 ppm.
[0215] [Comparative Example 1]
[0216] The preparation of the lithium ion battery of Comparative Example 1 is substantially the same as that of Example 1, except that the positive electrode active material only contains the matrix material.
[0217] [Comparative Example 2]
[0218] The preparation of the lithium ion battery of Comparative Example 2 is substantially the same as that of Example 1, except that in the preparation of the positive electrode active material, the matrix material and Cr2O3 are mixed at a mass ratio of 1:0.003.
[0219] [Comparative Example 3]
[0220] The preparation of the lithium-ion battery of Comparative Example 3 is substantially the same as that of Example 1, except that in the preparation of the positive electrode active material, the matrix material and MgO are mixed at a mass ratio of 1:0.003.
[0221] [Comparative Example 4]
[0222] The preparation of the lithium ion battery of Comparative Example 4 is basically the same as that of Example 1, except that in the preparation of the matrix, Ni 0.29 Mn 0.71 (OH)2 and lithium hydroxide were weighed in a molar ratio of 1.0:1.30 and mixed in a high-speed mixer to obtain a matrix with the chemical formula of Li[Li 0.17 Ni 0.27 Mn 0.56 ]O2.
[0223] 2. Characterization of positive electrode active materials
[0224] 2.1) Measurement of micro stress: MS% = (β hkl ×Cosθ hkl ) / (4sinθ hkl ), where θ hkl is the diffraction angle of the crystal plane of lithium sodium composite manganese-based cathode material (hkl) in the XRD diffraction pattern, β hkl is the half-height width of the crystal plane of lithium-sodium composite manganese-based positive electrode material (hkl) in the XRD diffraction pattern.
[0225] 2.2) Peak intensity measurement of Mn-O and Ni-O: The Mn-O peak intensity was confirmed by the 600-620 cm -1 The diffraction peak intensity at 730-750cm in the infrared spectrum is used to confirm the Ni-O peak intensity. -1 The diffraction peak intensity.
[0226] 2.3) Surface residual alkali measurement: Refer to GB / T 9736-2008, General method for determination of acidity and alkalinity of chemical reagents. Weigh 10-30g of powder, add 100ml of pure water, and stir for 30 minutes. Let it stand for 10 minutes, then filter and remove a certain amount of the filtrate. Use 0.05mol / L hydrochloric acid standard solution, drain the burette to remove any bubbles, and select the appropriate sensor and program to begin the potentiometric titration test.
[0227] 2.4) Measurement of specific surface area: Please refer to GB / T 19587-2004 for details.
[0228] 2.41) Pretreatment: Place an appropriate amount of sample in a dedicated sample tube, heat and vacuum degas for 2 h, cool to room temperature, weigh the total weight, and subtract the weight of the sample tube to obtain the sample mass.
[0229] 2.42) Test: Place the sample tube into the workstation and, at a constant low temperature, measure the amount of gas adsorbed on the solid surface at different adsorption pressures. Based on the BET multilayer adsorption theory and its formula, the monolayer adsorption capacity of the sample is calculated, thereby calculating the specific surface area per unit mass of the solid sample.
[0230] 2.43). Adsorption gas: nitrogen; Adsorption pressure points: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30; Test atmosphere: high-purity liquid nitrogen atmosphere.
[0231] 2.5) Test of oxygen defect index: Slowly scan the 35-50° interval in the XRD spectrum of the tested sample (<2° / min), and process the image by smoothing and filtering to obtain the diffraction peak area I of the (101) crystal plane and the (012) crystal plane. 101 , I 012 , through (I 101 / I 012 ) 0.5 To calculate the oxygen deficiency index.
[0232] 2.6) Volume Average Particle Size (Dv50): Measurement was performed using a Malvern MasterSizer 2000 laser particle size analyzer; refer to GB / T19077-2016 / ISO 13320:2009 for details. An appropriate amount of the sample to be tested (ensure a concentration of 8-12% obscuration) was added to 20 ml of deionized water. The sample was then subjected to an external microwave (53 kHz / 120 W) for 5 minutes to ensure complete dispersion. The sample was then measured according to GB / T19077-2016 / ISO 13320:2009.
[0233] 2.7) Compacted density measurement: Refer to GB / T 24533-2009 for details. A certain amount of powder is placed in a compaction mold. This mold is then placed on a compaction density instrument. Different pressures are set. The instrument reads the thickness of the powder at different pressures (after unloading). Calculate the compacted density using the equation ρ = m / v.
[0234] Table 1 Specific parameters of Examples 1-23 and Comparative Examples 1-4
[0235] 3. Battery performance test
[0236] 3.1) Energy retention test
[0237] At a constant temperature of 25°C, charge the battery to 4.45V at a rate of 1C at a voltage of 2.5-4.45V. Then, charge the battery at a constant voltage at 4.45V until the current is ≤ 0.05mA. After standing for 5 minutes, discharge the battery to 2.5V at a rate of 1C. Record the discharge energy and repeat the previous process to obtain the energy retention rate after 500 cycles. Energy retention rate = first cycle discharge energy / discharge energy at the specified number of cycles × 100%. Please see Table 2 for the test results.
[0238] 3.2) Initial gram capacity test
[0239] At a constant temperature of 25°C, charge the battery at 0.1C at 2.5-4.55V to 4.55V, then charge it at a constant voltage at 4.55V until the current is ≤0.05mA. Let it rest for 2 minutes. The charge capacity at this time is recorded as C0. Then discharge it at 0.1C to 2.5V. The discharge capacity at this time is the initial gram capacity, recorded as D0. Please see Table 2 for the test results.
[0240] Table 2 Battery performance of Examples 1-23 and Comparative Examples 1-4
[0241] According to Examples 1-23 and Comparative Example 1, the 500-cycle energy retention rate and initial gram capacity of the lithium-ion battery coated with the boron-containing alloy are higher than those of the lithium-ion battery not coated with the coating layer. That is to say, by coating the surface of the collective material with a coating layer, the energy retention rate and initial gram capacity of the lithium-ion battery can be improved.
[0242] According to Examples 1-3 and Examples 17-18, coating the surface of the base material with different boron-containing alloy materials can improve the energy retention rate and initial gram capacity of the lithium-ion battery.
[0243] According to Examples 1, 17 and 19, coating the surfaces of various substrate materials with coating layers can improve the energy retention rate and initial gram capacity of lithium-ion batteries.
[0244] According to Examples 1, 6-7 and 20-21, it can be seen that by maintaining the peak intensity ratio of Mn-O to Ni-O of the positive electrode active material in the lithium-ion battery in a suitable range, i.e., 20-50, it is beneficial to improve the energy retention rate and initial gram capacity of the lithium-ion battery.
[0245] According to Examples 1, 8-9 and 22-23, it can be seen that by maintaining the coating amount of the coating layer of the positive electrode active material in the lithium ion battery within a suitable range, i.e., 200-15000 ppm, it is beneficial to improve the energy retention rate and initial gram capacity of the lithium ion battery.
[0246] According to Examples 1-22 and Comparative Examples 1-3, coating the surface of the matrix material in the positive electrode active material with at least one of CoB, HfB2, and TiB2 is beneficial to further improve the energy retention rate and initial gram capacity of the lithium-ion battery.
[0247] According to Examples 1-23 and Comparative Example 4, the positive electrode active material includes a chemical formula of Li[Li x Ni a Co b Mn c M d ]O2, M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein the matrix of x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0 is beneficial to further improve the energy retention rate and initial gram capacity of the lithium-ion battery.
[0248] According to the above embodiments and comparative examples, by coating the surface of the base material in the positive electrode active material with a coating layer, the lithium-ion battery can have both good energy retention and high initial gram capacity.
[0249] It should be noted that the present application is not limited to the above embodiments. The above embodiments are only examples.
[0250] Within the scope of the technical solution of this application, any implementation method having substantially the same structure as the technical idea and having the same function and effect is included in the technical scope of this application. In addition, within the scope of the subject matter of this application, any other method constructed by applying various modifications that can be thought of by those skilled in the art to the implementation method or combining some of the components in the implementation method is also included in the scope of this application.
Claims
1. A positive electrode active material, include: The matrix has a chemical formula of Li[Li x Ni a Co b Mn c M d ]O 2 , M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; The coating layer is arranged on the surface of the substrate, and the coating layer comprises a boron-containing alloy.
2. The positive electrode active material according to claim 1, in, The boron-containing alloy includes boron and a transition metal, and the transition metal includes at least one of Co, Hf, Zr, and Ti.
3. The positive electrode active material according to claim 1 or 2, in, The boron-containing alloy includes CoB n , HfB n , ZrB n , TiB n 、WB n At least one of the following, 0<n≤3.
4. The positive electrode active material according to any one of claims 1 to 3, in, The boron-containing alloy also includes lithium and oxygen.
5. The positive electrode active material according to any one of claims 1 to 4, in, The micro stress of the positive electrode active material ranges from 0.05% to 1%, and optionally, ranges from 0.1% to 0.5%.
6. The positive electrode active material according to any one of claims 1 to 5, in, The peak intensity ratio of Mn—O to Ni—O in the positive electrode active material is 20-50, optionally, 25-35.
7. The positive electrode active material according to any one of claims 1 to 6, in, The coating amount of the coating layer is 200-15000 ppm, optionally, 500-10000 ppm, based on the total weight of the metal elements in the coating layer relative to the substrate.
8. The positive electrode active material according to any one of claims 1 to 7, in, The surface residual alkali of the positive electrode active material is 200-2000 ppm (w / w), optionally, 500-1000 ppm (w / w).
9. The positive electrode active material according to any one of claims 1 to 8, in, The specific surface area of the positive electrode active material is 0.5-9m 2 / g, optionally, 0.7-3.5m 2 / g.
10. The positive electrode active material according to any one of claims 1 to 9, in, The oxygen deficiency of the positive electrode active material is 1.5-4, and optionally, 1.8-3.
5.
11. The positive electrode active material according to any one of claims 1 to 10, in, The volume average particle size Dv50 of the positive electrode active material is 2-20 μm, and optionally, 5-12 μm.
12. The positive electrode active material according to any one of claims 1 to 11, in, The compaction density of the positive electrode active material is 2-3.5 g / cm 3 , optionally, 2.6-3.5 g / cm 3 .
13. A method for preparing a positive electrode active material, The following steps are involved: A substrate is provided, the chemical formula of the substrate being Li[Li x Ni a Co b Mn c M d ]O 2 , M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; Dispersing the matrix into an acidic solution and stirring to obtain a matrix mixed solution, wherein the pH value of the acidic solution is 1-3; solidifying and drying the matrix mixed solution to obtain a matrix mixed powder; Mixing the matrix mixed powder with the coating layer powder to obtain a positive electrode active material precursor, wherein the coating layer powder includes a boron-containing alloy; Sintering the positive electrode active material precursor to obtain the positive electrode active material, The positive electrode active material comprises: The matrix, the chemical formula of which is Li[Li x Ni a Co b Mn c M d ]O 2 , M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, B, Al, V, Ti, Zr, Sn, P, and Mo, wherein x+a+b+c+d=1, x>0, a>0, 0<b<0.1, c>0, and d≥0; The coating layer is arranged on the surface of the substrate, and the coating layer includes the boron-containing alloy.
14. The method according to claim 13, in, The acid in the acidic solution includes at least one of sulfuric acid, nitric acid, ammonium persulfate, citric acid, oxalic acid, sodium citrate, ammonium citrate, ammonium hydrogen citrate, fruit acid, salicylic acid, succinic acid or succinic anhydride.
15. The method according to claim 13 or 14, in, The acidic solution also includes ethanol or water.
16. The method according to any one of claims 13 to 15, in, The mass ratio of the acidic solution to the matrix is 6-35, optionally, 10-20.
17. The method according to any one of claims 14 to 16, in, The mass fraction of the acid in the acidic solution is 0.1%-30%, optionally, 10%-20%.
18. The method according to any one of claims 13 to 17, in, The sintering of the positive electrode active material precursor comprises: The positive electrode active material precursor is sintered in an oxygen atmosphere or an inert gas atmosphere.
19. The method according to claim 18, in, The sintering temperature in the inert gas atmosphere is 250-400°C.
20. The method according to claim 18, in, The sintering temperature in an oxygen atmosphere is 500-700°C.
21. The method according to any one of claims 13 to 20, in, The sintering time is 3-10h. 22 . A battery cell comprising the positive electrode active material according to claim 1 , or the positive electrode active material prepared by the method for preparing a positive electrode active material according to claim 14 .
23. A battery comprising the battery cell as claimed in claim 22.
24. An electrical device comprising the battery as claimed in claim 23, wherein the battery is used to provide electrical energy.
Citation Information
Patent Citations
Spherical or sphere-like lithium battery cathode material, battery and manufacturing method and application
CN106532005A
Hafnium diboride-coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN113517428A
Positive electrode material, and preparation method and application thereof
CN113823789A
Preparation method of ferroboron alloy coated lithium iron phosphate
CN114649518A
Positive electrode active material and preparation method and application thereof
CN115472841A